Ike [videorecording (DVD)] : countdown to D-Day - Harmon, Robert; Selleck, Tom, 1945-; Remar, James; Bottoms, Timothy, 1949- (Columbia TriStar Home Entertainment, 2004)
In March of 1944 recently appointed Supreme Commander of the Allied Forces, General Eisenhower, meets with Prime Minister Winston Churchill. They must come up with a brilliant strategy to put an end to World War II.